Development and characterization of noble metal integrated polymeric membrane reactors for three-phase hydrogenation reactions - Stanford, John Paul (Kansas State University, 2016)
Catalytic membrane reactors are a class of reactors that utilize a membrane to selectively deliver reactants to catalysts integrated in the membrane. The focus of this research has been on developing and characterizing polymeric catalytic membranes for three-phase hydrogenation reactions, where the membrane functions as a gas/liquid phase contactor allowing selective delivery of hydrogen through the membrane to reach catalytic sites located on the liquid side of the membrane. The benefit of conducting three-phase reactions in this manner is that delivering hydrogen through the membrane to reach catalytic sites avoids the necessity of hydrogen dissolution and diffusion in the liquid phase, which are both inherently low and often described as causing mass-transfer and reaction rate limitations for the reactive system. This work examines two types of membrane reactor systems, porous polytetrafluoroethylene and asymmetric Matrimid membranes, respectively, for the ruthenium catalyzed aqueous phase hydrogenation of levulinic acid. The highly hydrophobic PTFE material provides an almost impermeable barrier to the liquid phase while allowing hydrogen gas to freely transport through the pores to reach catalytic sites located at the liquid/membrane interface. Catalytic rates as a function of hydrogen pressure over the range 0.07 to 5.6 bar are presented and shown to be higher than those of a packed bed reactor under similar reaction conditions. An increasing catalytic benefit was obtained operating at temperatures up to 90 °C, which is attributed to increased hydrogen permeability and avoidance of the decreasing solubility of hydrogen in water with increasing temperature. The membrane reactor was shown to be stable with no decrease in catalytic activity over 200 hours of operation. The Matrimid membrane reactor work demonstrates the feasibility of applying an integrally-skinned asymmetric membrane for an aqueous phase hydrogenation reaction and focuses on the impact that membrane hydrogen permeance and catalyst loading have on catalytic activity. The non-porous nature of the separating layer in the Matrimid membrane allowed successful operation up to 150 °C. The overall catalytic rates were approximately an order of magnitude lower than those achieved in the PTFE membrane reactor system due primarily to significantly lower hydrogen permeances, nevertheless rates were still higher than control experiments. This work also focuses on characterizing Matrimid/solvent thermodynamic relationships for a variety of organic solvents, looking at sorption, diffusion, and polymer relaxation behavior in thin films ranging from 0.1 to 2.0 µm in thickness using quartz crystal microbalance techniques. Diffusion coefficients at infinite dilution for water and C1-C6 alcohols are given as a function of van der Waals molar volume and a clear dependency is shown ranging from 2E-11 to 6.5E-13 cm²/s for water and hexanol, respectively, for 0.26 µm thick films. Diffusion coefficients for all studied vapor penetrants displayed a marked dependence on thickness spanning approximately two orders of magnitude for each respective vapor penetrant over the range 0.1 to 1.0 µm. Chemically cross-linking Matrimid is a method to mitigate some of the relatively high sorption and swelling behavior exhibited in the presence of sorbing species. An in-depth analysis on the vapor phase ethylenediamine cross-linking of Matrimid films and its impact on diffusion, sorption, and relaxation is also described.
Keywords: Membrane; Membrane reactor; Three-phase hydrogenation; Levulinic acid; Diffusion; Polymer cross-linking